Innovation for Reducing Blood Culture Contamination: Initial Specimen Diversion Technique - Patton, Richard G. (American Society for Microbiology (ASM), 2010)
We hypothesized that diversion of the first milliliter of venipuncture blood—the initial specimen diversion technique (ISDT)—would eliminate incompletely sterilized fragments of skin from the culture specimen and significantly reduce our blood culture contamination rate (R). We studied our hypothesis prospectively beginning with our control culture (C) definition: one venipuncture with two sequentially obtained specimens, 10 ml each, the first specimen (M1) for aerobic and the second (M2) for anaerobic media. The test ISDT culture (D) was identical, with the exception that each was preceded by diverting a 1-ml sample (D(S)) from the same venipuncture. During the first of two sequential 9-month periods, we captured D versus C data (n = 3,733), where D(MX)R and C(MX)R are R for D and C specimens. Our hypothesis predicted D(S) would divert soiled skin fragments from D(M1), and therefore, C(M1)R would be significantly greater than D(M1)R. This was confirmed by C(M1)R (30/1,061 [2.8%]) less D(M1)R (37/2,672 [1.4%]; P = 0.005), which equals 1.4%. For the second 9-month follow-up period, data were compiled for all cultures (n = 4,143), where AD(MX)R is R for all (A) diversion specimens, enabling comparison to test ISDT. Our hypothesis predicted no significant differences for test ISDT versus all ISDT. This was confirmed by D(M 1)R (37/2,672 [1.4%]) versus AD(M 1)R (42/4,143 [1.0%]; P = 0.17) and D(M2)R (21/2,672 [0.80%]) versus AD(M2)R (39/4,143 [0.94%]; P = 0.50). We conclude that our hypothesis is valid: venipuncture needles soil blood culture specimens with unsterilized skin fragments and increase R, and ISDT significantly reduces R from venipuncture-obtained blood culture specimens.